2011
DOI: 10.4314/tjpr.v9i6.63593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anticaries Activity of Selected Mouthwash Marketed in Nigeria

Abstract: Purpose: This work was aimed at evaluating four brands of mouthwash marketed in Nigeria for their anticaries activity. Method: The susceptibility pattern of bacterial isolates obtained from 30 patients having carious teeth to the selected mouthwash was determined using the cup-plate method. The zones of inhibition produced by the mouthwash against the bacterial isolates were measured to determine the degree of susceptibility. Results: The organisms isolated from the patients were Staphylococccus aureus, Klebsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…The findings of BB Oluremiet.al [42] were, to some extent , in agreement with the results of current study . Table 4 and figure 6 profiles, the antibacterial susceptibility of the synthesis Zno/Nps dental composite in different concentrations (5%, 7%, 10%wt) which displayed that the activity against all isolated of bacterial species.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of BB Oluremiet.al [42] were, to some extent , in agreement with the results of current study . Table 4 and figure 6 profiles, the antibacterial susceptibility of the synthesis Zno/Nps dental composite in different concentrations (5%, 7%, 10%wt) which displayed that the activity against all isolated of bacterial species.…”
Section: Discussionsupporting
confidence: 83%
“…Zinc oxide is a safe bactericidal metallic oxide (inorganic agent) because it isnon-toxic to animal cells in low concentrations but is very toxic to bacteria, killing them, although, the metals and metallic oxides as zinc oxide, are considered toxic to human cells at highconcentrations, they do not seem to be toxic at very low concentrations on human cells [32,[39][40][41]. In present study that was conducted on (50) caries samples , 26 isolates of bacteria from all caries specimens showed positive results due to bacterial culturing of these samples which are positive for male and female patients respectively as seen in Table 2, anyhow, our results were consistent with workers [42] observation . in our study isolated four types of bacteria they consisted of Streptococcus mutans which was the most frequently isolated bacterial species (45.45%, 46.66%) followed by Staphylococcus aureus (27.27%, 26.66%); Pseudomonas areuginosa (18.18%, 20%) and Klebsiella.spp (9.09%, 6.66%) in all cases with percentage ratio respectively in male and female Table 3.…”
Section: Discussionsupporting
confidence: 81%
“…Cuesta et al, identified Staphylococcus species and Candida ablicans in dental caries and periodontal pockets in patients . Oluremi et al, found the prevalence of Staphylococcus , followed by S. mutans and Lactobacilli in dental caries . Additionally, Staphylococcus was isolated from dental caries in a secondary health care institution .…”
Section: Introductionmentioning
confidence: 99%
“…6 Oluremi et al, found the prevalence of Staphylococcus, followed by S. mutans and Lactobacilli in dental caries. 7 Additionally, Staphylococcus was isolated from dental caries in a secondary health care institution. 8 Microbial acid "low-pH" of nonmutans bacterial biofilms plays a threatening role to the plaque homeostasis by expediting a shift of the demineralization/remineralization balance from "net mineral gain" to "net mineral loss" (acidogenic stage).…”
mentioning
confidence: 99%
“…Insoluble glucans synthesized by S.mutans increase the pathogenicity of oral biofilm by promoting the adherence and accumulation of cariogenic bacteria on tooth surface 6 . This microorganism is also highly acidogenic and aciduric, meaning that they produce acids which can dissolve the tooth substance -calcium phosphate in the form of hydroxyapatite crystals -and that they can survive and produce acids in a low pH environment 7 .…”
Section: Introductionmentioning
confidence: 99%